REFLEKSI MAKNA KEADILAN PROFESI AKUNTAN DALAM PERSPEKTIF SPIRITUAL KRISTIANI - Fransiskus Randa (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2020)
This paper is a reflexisting of the justice as something that is always added and fought for by individuals and society. This article tries to find an equivalent meaning of justice in the Christian faith and tries to reflect the practices of justice in the real world. The results show that justice is a slogan that becomes the jargon of each individual or society but is very difficult to implement properly and consistently.